Long-term follow up of patients with hematological malignancies treated with total body irradiation using intensity modulated radiation therapy - Ladbury, Colton; Hao, Claire; Yang, Dongyun; Hui, Susanta; Han, Chunhui; Liu, An; Salhotra, Amandeep; Nakamura, Ryotaro; Rosenthal, Joseph; Stein, Anthony; Wong, Jeffrey; Dandapani, Savita (Frontiers in Oncology, 2022)
Background: With the advent of modern radiation treatment technologies such as intensity modulated radiation therapy (IMRT), there has been increasing interest in its use for total body irradiation (TBI) conditioning regimens for hematopoietic cell transplantation (HCT) to achieve lower doses to critical organs such as the lungs and kidneys. Although this has been reported on in early studies, long-term safety and efficacy data is limited. Methods: We performed a single institution matched-pair retrospective analysis of patients treated with IMRT TBI and standard TBI between 2010 and 2020 to provide data on long-term outcomes. Patients with hematologic malignancies, who could not tolerate standing for traditional TBI or who received prior radiation received IMRT TBI. Patients were matched based on age, diagnosis, disease status, and year of transplant, and were matched 2:1 to the standard TBI and IMRT TBI cohorts. Patient and treatment characteristics, toxicity, graft-versus-host disease (GVHD), dosimetry, and outcomes were evaluated for each cohort. Results: A total of 13 patients met inclusion criteria for the IMRT cohort, leading to 26 patients in the standard TBI cohort. There was no significant difference in relevant clinical factors between the cohorts. Reasons for using IMRT over conventional TBI included being unable to stand (n=5), prior radiation (n=5), and pediatric patient requiring anesthesia (n=3). Among living patients, median follow-up for all patients was 5.1 years in the IMRT TBI cohort and 5.5 years in the standard TBI cohort. The 5-yr estimate of OS was 68% in the IMRT TBI cohort and 60% in the standard TBI cohort (p=0.706). The 5-yr estimate of RFS was 54% in the IMRT TBI cohort and 60% in the standard TBI cohort (p=0.529). There was no clinically significant pneumonitis, nephritis, hypothyroidism, or cataracts reported in the IMRT TBI cohort. 41.7% of patients in the IMRT TBI cohort and 79.2% of patients in the standard TBI cohort experienced Grade II-IV acute GVHD (p=0.023). Conclusions: IMRT TBI appears to lead to favorable long-term outcome and dosimetry, and therefore potentially improved long-term toxicity profile compared to conventional TBI. IMRT TBI warrants further investigation as part of larger prospective trials.